Responsabilidade civil como função social na distribuição e revenda de combustível face ao direito do consumidor e ao meio ambiente - Fernandes, Clédina Maria (2013)
The civil liability of the distribution and retail fuel stems from the fact business activity developed to be high risk and can be said as risk inherent or latent danger that has predictability and normality characterized by placing the consumer in a position of vulnerability, such as the environment, both public policies defined and constitutional protection. Consumer protection as a fundamental right and the environment as the primacy of social order aims the welfare and social justice, as inserted right to the third dimension, are guarded by the State when it creates operational standards through public policies and indirectly intervenes in the economic order. This intervention is due to consumer protection and the environment are economic order principles, founded on free initiative and free competition, ensuring everyone a dignified existence which underlies the irradiation of fundamental rights in private initiative, before the commercial evaluation, mass consumption, the emergence of new technologies that link consumers to the environment before the protection of life, health and safety and ensuring a better quality of life for present and future generations. To repair this damage and the right to information are provided as fundamental rights that put the person at the epicenter of the relations and collective interest stands out against individual interests that to be done need public-private partnership. In such a way that the used methodology was an analysis of documents correlating them with bibliographic sources whose goals are to recognize the civil responsibility as limit to subjective right, having to develop a social function where guilt and risk grow distant and the damage is configured as a consequence of inherent risk, requiring the State interventional postures in fulfilling its public policy; prevailing in these risky activities the solidarity of those involved in the chain of production and socialization of damage forward those are provided directly of products of hazardous nature that put in a position of vulnerability the environment and the consumer